Carbon nanofiber catalytic membrane as well as preparation method and application thereof

By embedding Mn3O4 catalyst particles into the carbon nanofiber catalytic film to form a carbon nanofiber catalytic film with a graded pore structure, the problem that existing air purification materials cannot remove particulate matter and formaldehyde at the same time is solved, and an efficient air purification effect is achieved.

CN119869237APending Publication Date: 2025-04-25NANJING TECH UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510250064.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing air purification materials cannot efficiently remove particulate matter and formaldehyde in indoor air at the same time, and there are problems of insufficient catalytic efficiency and unstable filtration performance.

Method used

A carbon nanofiber catalytic membrane is adopted, which has a microporous-mesoporous-macroporous graded pore structure, and the catalyst particle Mn3O4 is embedded in the pore structure of the carbon nanofiber. By improving the structure and catalytic mechanism, high-efficiency filtration of particulate matter and room-temperature catalytic degradation of formaldehyde is achieved.

Benefits of technology

It realizes efficient filtration of indoor particulate matter and room temperature catalytic degradation of formaldehyde, improves air purification performance and improves air quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869237A_ABST
    Figure CN119869237A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nanofiber catalytic membrane applicable to the field of air purification as well as a preparation method and application of the carbon nanofiber catalytic membrane. The catalytic membrane is prepared by taking polyacrylonitrile as a carbon source, manganese nitrate as a catalyst precursor and polystyrene as a pore-forming agent through the steps of electrostatic spinning, pre-oxidation, carbonization and atmosphere conversion oxidation. The prepared carbon nanofiber catalytic membrane has a hierarchical pore structure of micropores, mesopores and macropores, the crystalline phase of the catalyst is Mn3O4, the particle size of the catalyst is small, and catalyst particles are highly dispersed in a carbon nanofiber matrix. The obtained carbon nanofiber catalytic membrane has the dual-function air purification performance of particulate matter filtration and formaldehyde room-temperature catalytic degradation, the PM2.5 filtration efficiency reaches up to 99%, and the formaldehyde catalytic efficiency at room temperature is 80% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon nanofiber catalytic membrane and a preparation method and application thereof, belonging to the technical field of membrane material preparation. Background Art

[0002] With the acceleration of industrialization and the rapid development of urbanization, air pollution is becoming increasingly serious, especially particulate matter (PM) and volatile organic compounds (such as formaldehyde), which pose an increasingly prominent threat to the environment and human health. Particulate matter not only causes respiratory diseases, but also has serious effects on the cardiovascular system, while formaldehyde is a common indoor pollutant that has been identified as a possible human carcinogen by the International Agency for Research on Cancer (IARC). Particulate matter and formaldehyde often coexist in indoor air, and existing air purification materials can only remove one pollutant. Therefore, it is particularly important to develop efficient and multifunctional air purification technology.

[0003] In recent years, the research and development of multifunctional air purification materials has begun to be explored. For example, patent CN107503044B discloses a method for preparing a silica nanofiber composite membrane loaded with ZIF-8 for air purification, which uses the high specific surface area of ​​zeolite imidazolate framework structure material (ZIF-8) to achieve efficient capture of PM2.5 and formaldehyde adsorption during air purification; patent CN111013271B discloses a nanofiber-loaded metal organic framework air purification material and its preparation method. This polystyrene nanofiber-loaded metal organic framework material not only has good filtering performance, but also has gas adsorption performance, and can adsorb volatile organic matter such as formaldehyde. However, there are problems such as adsorption capacity limitation in removing formaldehyde by adsorption, and secondary pollution will be caused after formaldehyde desorption. In contrast, formaldehyde room temperature catalysis can directly decompose formaldehyde into carbon dioxide and water in situ, achieving complete removal of formaldehyde molecules, so it has more development potential.

[0004] Carbon nanomaterials have shown broad application prospects in the field of environmental governance due to their excellent physical and chemical properties. As a new type of carbon nanomaterial, carbon nanofiber membrane has a large specific surface area, good conductivity and excellent mechanical strength, and has been widely used in catalysis, filtration and sensors. Although existing studies have shown the good performance of carbon nanofibers in air pollutant purification, the existing technology still has problems such as insufficient catalytic efficiency and unstable filtration performance. Therefore, it is urgent to further optimize the structure and function of carbon nanofibers to improve their application performance in air purification.

[0005] In response to the above problems, this application aims to develop a new type of carbon nanofiber catalytic membrane, which can achieve efficient removal of particulate matter and formaldehyde by improving its structure and catalytic mechanism, thereby effectively improving air quality. Summary of the invention

[0006] In view of the problem that existing air purification materials cannot achieve multifunctional air purification applications, the present invention provides a method for preparing a carbon nanofiber catalytic membrane, which improves its structure and catalytic mechanism to simultaneously achieve efficient filtration of particulate matter in indoor air and catalytic degradation of formaldehyde at room temperature, thereby effectively improving air quality.

[0007] The technical solution adopted by the present invention is:

[0008] A carbon nanofiber catalytic membrane has a hierarchical pore structure of micropores-mesopores-macropores, and catalyst particles are distributed in the pore structure of the carbon nanofibers. The crystal phase of the catalyst particles is Mn3O4 and the particle size is 1-10nm.

[0009] The preparation method of the above-mentioned carbon nanofiber catalytic membrane is to dissolve the pore-forming agent and then dissolve the carbon source and manganese salt in sequence to obtain a spinning solution, and then pre-oxidize the precursor nanofiber membrane after electrostatic spinning. In order to avoid the structural collapse of the electrostatic spinning nanofiber membrane after carbonization, the precursor nanofiber membrane must be pre-oxidized. The pre-oxidation promotes the cyclization reaction of the organic carbon chain to initially form a heat-resistant ladder structure, so that it will not be cracked in the subsequent carbonization process, and play the role of fixing oxygen and carbon. Afterwards, the pre-oxidized membrane is placed in nitrogen or an inert atmosphere for carbonization, and further dehydrogenated during carbonization to form a standard high-temperature resistant graphite ring structure, and then the carbonized membrane is placed in an air atmosphere for heat treatment to obtain the catalytic membrane. If it is directly carbonized without pre-oxidation, polymers such as resins will generate resin carbon due to high-temperature pyrolysis and chain scission.

[0010] Preferably, the pore-forming agent is polystyrene and the carbon source is polyacrylonitrile;

[0011] In the spinning solution, the contents of polystyrene, polyacrylonitrile and manganese salt are 5-20wt%, 10-30wt% and 1-10wt% respectively.

[0012] Preferably, the manganese salt is any one of manganese nitrate, manganese chloride, manganese acetate and manganese sulfate.

[0013] Preferably, the conditions for electrospinning are: spinning voltage 10-30 kV, injection speed 0.06-0.2 mm / min, receiving distance 10-30 cm, spinning temperature 20-30° C., spinning humidity 20-60 RH%, and spinning time 1.5-3.5 h.

[0014] Preferably, after obtaining the precursor nanofiber membrane, a drying step is performed, and the drying temperature is 50-80°C.

[0015] Preferably, the pre-oxidation conditions are: in an air atmosphere, heating to 220-350° C. at a heating rate of 0.5-10° C. / min, and keeping the temperature for 1-3 hours.

[0016] Preferably, the carbonization conditions are: firstly maintaining at 350-500° C. for 0.5-1.5 h; then heating to 500-1000° C. at a heating rate of 1-10° C. / min, and carbonizing for 1-5 h.

[0017] Preferably, the heat treatment conditions are: 150-350°C, 10-60min.

[0018] The above-mentioned carbon nanofiber catalytic membrane is used in air purification for efficient filtration of particulate matter in the air and catalytic degradation of formaldehyde at room temperature.

[0019] The beneficial effects of the present invention are:

[0020] The carbon nanofiber catalytic membrane provided by the present invention has a hierarchical pore structure of micropores, mesopores and macropores. The catalyst particles are embedded in the rich pore structure of the carbon nanofibers. The key factors affecting the pore structure are the amount of polystyrene added and the constant temperature process at 450°C during carbonization. Polystyrene helps to construct a microporous structure on the fiber surface, and the constant temperature process at 450°C is conducive to the formation of a mesoporous structure. Due to the confining effect of the carbon matrix, the size of the prepared catalyst particles is extremely small, 5nm. At the same time, the amount of manganese added has a great influence on the size of the prepared catalyst particles. When the amount of manganese added is too much, the dispersion of the catalyst particles is low, and agglomeration is prone to occur, which in turn affects the filtration and catalytic performance of the membrane. The ultra-small catalyst and hierarchical pore structure enable the carbon nanofiber catalytic membrane to have excellent and rapid formaldehyde room temperature catalytic performance. The carbon nanofiber catalytic membrane has multifunctional air purification performance and can simultaneously achieve indoor particulate matter filtration and formaldehyde room temperature catalytic degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a photograph of the carbon nanofiber catalytic membrane prepared in Example 1;

[0022] Figure 2 This is a scanning electron microscope photograph of the carbon nanofiber catalytic membrane prepared in Example 1. The mesoporous structure on the surface of the nanofiber can be clearly observed;

[0023] Figure 3 This is a transmission electron microscope photo of the carbon nanofiber catalyst membrane prepared in Example 1. It can be observed that the size of the Mn3O4 particles is less than 5nm;

[0024] Figure 4 This is a scanning electron microscope photograph of the carbon nanofiber catalytic membrane prepared in Comparative Example 1. The surface of the nanofiber without polystyrene is relatively smooth, and no obvious micropores or mesopores can be observed;

[0025] Figure 5 This is a scanning electron microscope photograph of the carbon nanofiber catalytic membrane prepared in Comparative Example 2. The mesoporous structure on the surface of the nanofiber that was not kept at a constant temperature of 450° C. cannot be clearly observed;

[0026] Figure 6 This is a photo of the carbon nanofiber catalytic membrane prepared in Comparative Example 3. The macroscopic structure of the carbon nanofiber catalytic membrane that was not pre-oxidized has shrunk and its mechanical strength has been greatly reduced;

[0027] Figure 7 This is a scanning electron microscope photograph of the carbon nanofiber catalytic membrane prepared in Example 2. Compared with the carbon nanofiber catalytic membrane prepared in Example 1, the size of the catalyst on the surface of the nanofiber is larger;

[0028] Figure 8 This is a scanning electron microscope photograph of the carbon nanofiber catalytic membrane prepared in Example 3. Compared with the carbon nanofiber catalytic membrane prepared in Example 1, the catalyst on the surface of the nanofibers is larger in size and has a lower dispersion;

[0029] Fig. 9 This is the XRD spectrum of the carbon nanofiber catalyst membrane prepared in Example 1. The XRD data show that the crystal phase of the catalyst is Mn3O4. The PDF card is: 24-0734;

[0030] Fig.10 is the pore size distribution of the carbon nanofiber catalytic membrane prepared in Example 1, the pore size of the carbon nanofiber catalytic membrane is 1.8 μm;

[0031] Fig.11 The filtration efficiency of the carbon nanofiber catalytic membrane prepared in Example 1 for different particulate matter is 99.78% for PM2.5, 98.19% for PM0.3, and the pressure drop is 173.5 Pa;

[0032] Fig.12 The room temperature catalytic efficiency of the carbon nanofiber catalytic membrane prepared in Example 1 to formaldehyde can reach 80%. DETAILED DESCRIPTION

[0033] Example 1

[0034] The preparation method of the carbon nanofiber catalytic membrane is as follows:

[0035] Spinning solution configuration

[0036] 10% polystyrene by mass was dissolved in N,N-dimethylformamide (DMF) by heating and stirring at 80°C, and then 20% polyacrylonitrile powder by mass was added, and heating and stirring were continued until dissolved at a stirring speed of 500r / min, and then 2% manganese nitrate by mass was added until it was completely dissolved.

[0037] Electrospinning

[0038] The spinning voltage was 15.5 kV, the injection speed was 0.113 mm / min, the receiving distance was 15 cm, the spinning temperature was 25° C., the spinning humidity was 40 RH%, and the spinning time was 2 h. The precursor nanofiber membrane obtained by spinning was dried at 60° C. for use.

[0039] Pre-oxidation

[0040] The precursor nanofiber membrane was slowly heated to 280°C in an air atmosphere and maintained for 2 h at a heating rate of 1.0°C / min.

[0041] Carbonization

[0042] The nanofiber membrane after pre-oxidation treatment is subjected to carbonization heat treatment in a nitrogen or argon atmosphere. The carbonization process is first maintained at 450°C for 1 hour to ensure the decomposition of polystyrene and the formation of a mesoporous structure on the surface of the nanofiber membrane; then it is carbonized at 600°C for 2 hours to cause the carbon matrix to undergo graphitization transformation. The carbonization heating rate is 10°C / min.

[0043] Atmosphere oxidation

[0044] The carbonized nanofiber membrane obtained above was further heat-treated in an air atmosphere, and this process converted the zero-valent manganese element into Mn3O4. The heat treatment time was 20 minutes and the heat treatment temperature was 300°C.

[0045] Figure 1 is a photo of the prepared carbon nanofiber catalytic membrane; Figure 2 This is a scanning electron microscope photo of the prepared carbon nanofiber catalytic membrane. The mesoporous structure on the surface of the nanofiber can be clearly observed. Figure 3 This is a transmission electron microscope photo of the prepared carbon nanofiber catalyst membrane. It can be observed that the size of the Mn3O4 particles is less than 5nm; Fig. 9 This is the XRD spectrum of the prepared carbon nanofiber catalyst membrane. The XRD data show that the crystal phase of the catalyst is Mn3O4. The PDF card is: 24-0734; Fig.10 The pore size distribution of the prepared carbon nanofiber catalytic membrane is 1.8 μm.

[0046] Comparative Example 1

[0047] The preparation method of the carbon nanofiber catalytic membrane is as follows:

[0048] Spinning solution configuration

[0049] 20% by mass of polyacrylonitrile powder was heated and stirred at 80° C. and dissolved in N,N-dimethylformamide (DMF) at a stirring speed of 500 r / min, and then 2% by mass of manganese nitrate was added until it was completely dissolved.

[0050] Electrospinning

[0051] The spinning voltage was 15.5 kV, the injection speed was 0.113 mm / min, the receiving distance was 15 cm, the spinning temperature was 25° C., the spinning humidity was 40 RH%, and the spinning time was 2 h. The precursor nanofiber membrane obtained by spinning was dried at 60° C. for use.

[0052] Pre-oxidation

[0053] The precursor nanofiber membrane was slowly heated to 280°C in an air atmosphere and maintained for 2 h at a heating rate of 1.0°C / min.

[0054] Carbonization

[0055] The nanofiber membrane after pre-oxidation treatment is subjected to carbonization heat treatment in a nitrogen or argon atmosphere. The carbonization process is first maintained at 450°C for 1 hour to ensure the decomposition of polystyrene and the formation of a mesoporous structure on the surface of the nanofiber membrane; then it is carbonized at 600°C for 2 hours to cause the carbon matrix to undergo graphitization transformation. The carbonization heating rate is 10°C / min.

[0056] Atmosphere oxidation

[0057] The carbonized nanofiber membrane obtained above was further heat-treated in an air atmosphere, and this process converted the zero-valent manganese element into Mn3O4. The heat treatment time was 20 minutes and the heat treatment temperature was 300°C.

[0058] Figure 4 This is a scanning electron microscope photograph of the carbon nanofiber catalytic membrane prepared in Comparative Example 1. The surface of the nanofiber without polystyrene is relatively smooth, and no obvious micropores or mesopores can be observed.

[0059] Comparative Example 2

[0060] The preparation method of the carbon nanofiber catalytic membrane is as follows:

[0061] Spinning solution configuration

[0062] 10% polystyrene by mass was dissolved in N,N-dimethylformamide (DMF) by heating and stirring at 80°C, and then 20% polyacrylonitrile powder by mass was added, and heating and stirring were continued until dissolved at a stirring speed of 500r / min, and then 2% manganese nitrate by mass was added until it was completely dissolved.

[0063] Electrospinning

[0064] The spinning voltage was 15.5 kV, the injection speed was 0.113 mm / min, the receiving distance was 15 cm, the spinning temperature was 25° C., the spinning humidity was 40 RH%, and the spinning time was 2 h. The precursor nanofiber membrane obtained by spinning was dried at 60° C. for use.

[0065] Pre-oxidation

[0066] The precursor nanofiber membrane was slowly heated to 280°C in an air atmosphere and maintained for 2 h at a heating rate of 1.0°C / min.

[0067] Carbonization

[0068] The nanofiber membrane after pre-oxidation treatment is subjected to carbonization heat treatment in a nitrogen or argon atmosphere. The carbonization process is carbonized at 600°C for 2h to cause graphitization of the carbon matrix. The carbonization heating rate is 10°C / min.

[0069] Atmosphere oxidation

[0070] The carbonized nanofiber membrane obtained above was further heat-treated in an air atmosphere, and this process converted the zero-valent manganese element into Mn3O4. The heat treatment time was 20 minutes and the heat treatment temperature was 300°C.

[0071] Figure 5 This is a scanning electron microscope photograph of the carbon nanofiber catalytic membrane prepared in Comparative Example 2. The mesoporous structure on the surface of the nanofiber that was not kept at a constant temperature of 450° C. cannot be clearly observed.

[0072] Comparative Example 3

[0073] The preparation method of the carbon nanofiber catalytic membrane is as follows:

[0074] Spinning solution configuration

[0075] 10% polystyrene by mass was dissolved in N,N-dimethylformamide (DMF) by heating and stirring at 80°C, and then 20% polyacrylonitrile powder by mass was added, and heating and stirring were continued until dissolved at a stirring speed of 500r / min, and then 2% manganese nitrate by mass was added until it was completely dissolved.

[0076] Electrospinning

[0077] The spinning voltage was 15.5 kV, the injection speed was 0.113 mm / min, the receiving distance was 15 cm, the spinning temperature was 25° C., the spinning humidity was 40 RH%, and the spinning time was 2 h. The precursor nanofiber membrane obtained by spinning was dried at 60° C. for use.

[0078] Carbonization

[0079] The electrospun nanofiber membrane was carbonized in a nitrogen or argon atmosphere. The carbonization process was first maintained at 450°C for 1 hour to ensure the decomposition of polystyrene and the formation of a mesoporous structure on the surface of the nanofiber membrane. The carbonization was then continued at 600°C for 2 hours to cause the carbon matrix to undergo graphitization. The carbonization heating rate was 10°C / min.

[0080] Atmosphere oxidation

[0081] The carbonized nanofiber membrane obtained above was further heat-treated in an air atmosphere, and this process converted the zero-valent manganese element into Mn3O4. The heat treatment time was 20 minutes and the heat treatment temperature was 300°C.

[0082] Figure 6 This is a photograph of the carbon nanofiber catalytic membrane prepared in Comparative Example 3. The macroscopic structure of the carbon nanofiber catalytic membrane that has not been pre-oxidized has shrunk and its mechanical strength has been greatly reduced.

[0083] Example 2

[0084] The preparation method of the carbon nanofiber catalytic membrane is as follows:

[0085] Spinning solution configuration

[0086] 10% polystyrene by mass was dissolved in N,N-dimethylformamide (DMF) by heating and stirring at 80°C, and then 20% polyacrylonitrile powder by mass was added, and heating and stirring were continued until dissolved at a stirring speed of 500r / min, and then 5% manganese nitrate by mass was added until it was completely dissolved.

[0087] Electrospinning

[0088] The spinning voltage was 15.5 kV, the injection speed was 0.113 mm / min, the receiving distance was 15 cm, the spinning temperature was 25° C., the spinning humidity was 40 RH%, and the spinning time was 2 h. The precursor nanofiber membrane obtained by spinning was dried at 60° C. for use.

[0089] Pre-oxidation

[0090] The precursor nanofiber membrane was slowly heated to 280°C in an air atmosphere and maintained for 2 h at a heating rate of 1.0°C / min.

[0091] Carbonization

[0092] The nanofiber membrane after pre-oxidation treatment is subjected to carbonization heat treatment in a nitrogen or argon atmosphere. The carbonization process is first maintained at 450°C for 1 hour to ensure the decomposition of polystyrene and the formation of a mesoporous structure on the surface of the nanofiber membrane; then it is carbonized at 600°C for 2 hours to cause the carbon matrix to undergo graphitization transformation. The carbonization heating rate is 10°C / min.

[0093] Atmosphere oxidation

[0094] The carbonized nanofiber membrane obtained above was further heat-treated in an air atmosphere, and this process converted the zero-valent manganese element into Mn3O4. The heat treatment time was 20 minutes and the heat treatment temperature was 300°C.

[0095] Figure 7 This is a scanning electron microscope photograph of the carbon nanofiber catalytic membrane prepared in Example 2. Compared with the carbon nanofiber catalytic membrane prepared in Example 1, the size of the catalyst on the surface of the nanofiber is larger.

[0096] Example 3

[0097] The preparation method of the carbon nanofiber catalytic membrane is as follows:

[0098] Spinning solution configuration

[0099] 10% polystyrene by mass was dissolved in N,N-dimethylformamide (DMF) by heating and stirring at 80°C, and then 20% polyacrylonitrile powder by mass was added, and heating and stirring were continued until dissolved at a stirring speed of 500r / min, and then 10% manganese nitrate by mass was added until it was completely dissolved.

[0100] Electrospinning

[0101] The spinning voltage was 15.5 kV, the injection speed was 0.113 mm / min, the receiving distance was 15 cm, the spinning temperature was 25° C., the spinning humidity was 40 RH%, and the spinning time was 2 h. The precursor nanofiber membrane obtained by spinning was dried at 60° C. for use.

[0102] Pre-oxidation

[0103] The precursor nanofiber membrane was slowly heated to 280°C in an air atmosphere and maintained for 2 h at a heating rate of 1.0°C / min.

[0104] Carbonization

[0105] The nanofiber membrane after pre-oxidation treatment is subjected to carbonization heat treatment in a nitrogen or argon atmosphere. The carbonization process is first maintained at 450°C for 1 hour to ensure the decomposition of polystyrene and the formation of a mesoporous structure on the surface of the nanofiber membrane; then it is carbonized at 600°C for 2 hours to cause the carbon matrix to undergo graphitization transformation. The carbonization heating rate is 10°C / min.

[0106] Atmosphere oxidation

[0107] The carbonized nanofiber membrane obtained above was further heat-treated in an air atmosphere, and this process converted the zero-valent manganese element into Mn3O4. The heat treatment time was 20 minutes and the heat treatment temperature was 300°C.

[0108] Figure 8 This is a scanning electron microscope photograph of the carbon nanofiber catalytic membrane prepared in Example 3. Compared with the carbon nanofiber catalytic membrane prepared in Example 2, the catalyst on the surface of the nanofibers has a larger size and a lower dispersion.

[0109] Compared with Example 1, the preparation condition changed in Comparative Example 1 is the amount of polystyrene added. In Example 1, the amount of polystyrene added is 10%, and the prepared carbon nanofiber catalyst membrane has a hierarchical pore structure of micropores-mesopores-macroporous; in Comparative Example 1, the amount of polystyrene added is 0%, and the pore structure of the prepared carbon nanofiber catalyst membrane is mostly macropores, with very few micropores and mesopores.

[0110] Compared with Example 1, the preparation condition changed in Comparative Example 2 is the carbonization process. In Example 1, the carbonization process is first maintained at 450°C for 1 hour to ensure that polystyrene is decomposed and a mesoporous structure is formed on the surface of the nanofiber membrane, and then carbonized at 600°C for 2 hours. The prepared carbon nanofiber catalytic membrane has a hierarchical pore structure of micropores-mesopores-macroporous; the carbonization process in Comparative Example 1 is directly carbonized at 600°C for 2 hours. The pore structure of the prepared carbon nanofiber catalytic membrane is mostly macropores, a small amount is micropores, and the mesoporous structure is very small.

[0111] Compared with Example 1, the changed preparation condition in Comparative Example 3 is the pre-oxidation process. In Example 1, the precursor nanofiber membrane is slowly heated to 280°C in an air atmosphere and maintained for 2 hours, and the prepared carbon nanofiber catalytic membrane has synergistic purification performance; the precursor nanofiber membrane in Comparative Example 1 is not pre-oxidized, and the prepared carbon nanofiber catalytic membrane has a shrunk structure and a greatly reduced mechanical strength, and cannot be tested for filtration and catalytic performance.

[0112] Compared with Example 1, the preparation conditions changed in Examples 2 and 3 are all the addition amount of manganese source. In Example 1, the addition amount of manganese source is 2%, and the pore structure of the prepared carbon nanofibers is distributed with catalyst particles, with high dispersion, and the crystal phase of the catalyst particles is Mn3O4, and the particle size is below 5nm; in Example 2, the addition amount of manganese source is 5%, and the particle size of the catalyst particles is above 10nm, and in Example 3, the addition amount of manganese source is 10%, and the particle size of the catalyst particles is above 50nm, and the catalyst particles are agglomerated, and the dispersion is reduced.

[0113] Particle filtration

[0114] The particle filtration test was performed using an automatic filtration tester (Huada LZX-K1), which can provide simulated particles (sodium chloride aerosol, with a diameter less than 2.5 μm). The effective test area of ​​each sample is 25 cm 2 , the air flow rate is 5.33cm / s, the filtration efficiency is obtained according to the particle concentration at the inlet and outlet, and the pressure drop is detected by an electronic pressure sensor. The carbon nanofiber catalytic membrane prepared in Example 1 has a hierarchical pore structure of micropores-mesopores-macroporous, which increases the specific surface area and thus has excellent filtration efficiency; the pore structure of the carbon nanofiber catalytic membrane prepared in Comparative Examples 1 and 2 is mostly macropores, resulting in a decrease in specific surface area, and thus a decrease in filtration performance. Fig.11 The filtration efficiency of the carbon nanofiber catalytic membrane prepared in Example 1 for different particulate matter is 99.78% for PM2.5, 98.19% for PM0.3, and the pressure drop is 173.5 Pa.

[0115] Formaldehyde Catalysis

[0116] The sample was placed in a U-tube glass apparatus at an ambient temperature of 25°C. The gas flow rate was adjusted by a mass flow controller to simulate wind speed. The air passed through a bubbler containing paraformaldehyde and then mixed with another stream of air to control the inlet concentration of formaldehyde during the catalytic process. The formaldehyde concentration at the inlet and outlet was recorded using a British PPM htV-M recording formaldehyde detector. The catalytic performance will be affected by conditions such as the microstructure of the membrane, the particle size of the catalyst, and the catalyst loading. The carbon nanofiber catalytic membrane prepared in Example 1 has a hierarchical pore structure of micropores, mesopores and macropores, the catalyst crystal phase is Mn3O4, the catalyst particle size is below 5nm, the catalyst particles are highly dispersed in the carbon nanofiber matrix, the smaller catalyst size and higher catalyst dispersion increase the specific surface area and active sites of the catalyst, and thus the catalytic membrane has excellent formaldehyde catalytic performance; the carbon nanofiber catalytic membrane structure prepared in Comparative Example 1 shrinks, the mechanical strength is greatly reduced, and filtration and catalytic performance tests cannot be performed; the particle size of the catalyst particles in the carbon nanofiber catalytic membrane prepared in Example 2 is above 10nm, resulting in a reduction in the specific surface area and active sites of the catalyst, and thus the formaldehyde catalytic performance of the catalytic membrane decreases; the particle size of the catalyst particles in the carbon nanofiber catalytic membrane prepared in Example 3 is above 50nm, the catalyst particles agglomerate, and the dispersion decreases, resulting in a reduction in the specific surface area and active sites of the catalyst, and a reduction in dispersion, and thus the formaldehyde catalytic performance of the catalytic membrane decreases. Fig.12 The room temperature catalytic efficiency of the carbon nanofiber catalytic membrane prepared in Example 1 to formaldehyde can reach 80%.

[0117] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A carbon nanofiber catalytic membrane, characterized in that: The catalytic membrane has a hierarchical pore structure of micropores-mesopores-macropores, and catalyst particles are distributed in the pore structure of the carbon nanofibers. The crystal phase of the catalyst particles is Mn3O4, and the particle size is 1-10nm.

2. The method for preparing the carbon nanofiber catalytic membrane according to claim 1, characterized in that: The pore-forming agent is dissolved and then dissolved in a carbon source and a manganese salt in sequence to obtain a spinning solution. The precursor nanofiber membrane is obtained by electrospinning and then pre-oxidized. The precursor nanofiber membrane is then carbonized in a nitrogen or inert atmosphere and heat-treated in an air atmosphere to obtain the catalytic membrane.

3. The method for preparing the carbon nanofiber catalytic membrane according to claim 2, characterized in that: The pore former is polystyrene. The carbon source is polyacrylonitrile; In the spinning solution, the contents of polystyrene, polyacrylonitrile and manganese salt are 5-20wt%, 10-30wt% and 1-10wt% respectively.

4. The method for preparing the carbon nanofiber catalytic membrane according to claim 2, characterized in that: The manganese salt is any one of manganese nitrate, manganese chloride, manganese acetate and manganese sulfate.

5. The method for preparing the carbon nanofiber catalytic membrane according to claim 2, characterized in that: The conditions for electrospinning are: spinning voltage 10-30 kV, injection speed 0.06-0.2 mm / min, receiving distance 10-30 cm, spinning temperature 20-30° C., spinning humidity 20-60 RH%, spinning time 1.5-3.5 h.

6. The method for preparing a carbon nanofiber catalytic membrane according to claim 2, characterized in that: After obtaining the precursor nanofiber membrane, a drying step is performed at a temperature of 50-80°C.

7. The method for preparing a carbon nanofiber catalyst membrane according to claim 2, characterized in that: The pre-oxidation conditions are: In air atmosphere, heat to 220-350°C at a heating rate of 0.5-10°C / min and keep warm for 1-3h.

8. The method for preparing a carbon nanofiber catalyst membrane according to claim 2, characterized in that: The carbonization conditions are: first maintain at 350-500°C for 0.5-1.5h; then heat to 500-1000°C at a heating rate of 1-10°C / min, and carbonize for 1-5h.

9. The method for preparing a carbon nanofiber catalyst membrane according to claim 2, characterized in that: The heat treatment conditions are: 150-350℃, 10-60min.

10. The use of the carbon nanofiber catalytic membrane according to claim 1 in air purification, characterized in that: Used for high-efficiency filtration of particulate matter in the air and catalytic degradation of formaldehyde at room temperature.

Citation Information

Patent Citations

  • Preparation method of ZIF-8 loaded silica nanofiber membrane for air purification

    CN107503044B